2015
DOI: 10.1016/j.proeng.2015.08.986
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Location and Settings of Pressure Reducing Valves in Water Distribution Networks for Minimizing Water Losses

Abstract: The determination of the optimal location and settings of PRV is an operational problem that water utilities must deal with in order to reduce the real losses that are inherent to their water distribution system. In this research, a multi-objective optimization approach was developed to provide an optimal solution for the addressed problem, using the well-known metaheuristic algorithm NSGA-II and including the usage of hydraulic criteria to reduce the solution space, in order to enhance the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…To consider the effect of water losses when solving the hydraulic problem in water pressurized networks, some commercial software has been developed [48]. One of the solutions to allow for minimizing water losses is pressure reduction in a water supply network [49]. Stringent monitoring of the water distribution network reduces water losses considerably [50].…”
Section: The Methods For Assessing the Water Supply Network Reliabilitymentioning
confidence: 99%
“…To consider the effect of water losses when solving the hydraulic problem in water pressurized networks, some commercial software has been developed [48]. One of the solutions to allow for minimizing water losses is pressure reduction in a water supply network [49]. Stringent monitoring of the water distribution network reduces water losses considerably [50].…”
Section: The Methods For Assessing the Water Supply Network Reliabilitymentioning
confidence: 99%
“…The results showed that the scheme was able to maximize the energy produced by PATs. The non-dominated sorted genetic algorithm was used in [21,36,66] to solve the multi-objective optimization problems. The optimization problems were formulated to reduce the number of valves used and to also determine their optimal operation.…”
Section: Optimal Controlmentioning
confidence: 99%
“…In the literature, diaphragm pressure-reducing valves have been extensively investigated, from device modelling, possibly in combination with an electronic control apparatus [18][19][20][21][22][23][24] also under transient regimes [25], to the optimisation of their location in networks and their setting value [26][27][28][29][30][31][32][33][34][35][36][37]. The efficiency of the use of PRVs in reducing losses has been demonstrated in several studies [13,14,16,17,38].…”
Section: Introductionmentioning
confidence: 99%